Healthcare and aging: do European Union countries differ?. Issue 8 (10th October 2016) - Stankunas, Mindaugas; Avery, Mark; Lindert, Jutta; Edwards, Ian; Rosa, Mirko Di; Torres-Gonzalez, Francisco; Ioannidi-Kapolou, Elisabeth; Barros, Henrique; Soares, Joaquim
Abstract : Purpose: The purpose of this paper is to evaluate socio-economic inequalities in the use, accessibility and satisfaction with health services amongst 60-84 year old people from seven European urban communities. Design/methodology/approach: Data for this study were collected in 2009. The target population was people aged 60-84 years from Stuttgart (Germany), Athens (Greece), Ancona (Italy), Kaunas (Lithuania), Porto (Portugal), Granada (Spain) and Stockholm (Sweden). The total sample comprised 4, 467 respondents with a mean response rate across these countries of 45.2 per cent. Findings: The study demonstrated that the majority of respondents had contact with a health care provider within the last 12 months. The highest percentages were reported by respondents from Spain (97.8 per cent) and Portugal (97.7 per cent). The results suggest that 13.0 per cent of respondents had refrained from seeking care services. The highest rates were amongst seniors from Lithuania (24.0 per cent), Germany (16.2 per cent) and Portugal (15.4 per cent). Logistic regression suggests that seniors who refrained from seeking health care was statistically significant associated with those with higher levels of education (odds ratios (OR)=1.21; 95 per cent confidence intervals (CI)=1.01-1.25) and financial strain (OR=1.26; 95 per cent CI=1.16-1.37). Furthermore, the majority of respondents were satisfied with health care services. Originality/value: The findings from the "Elder Abuse: a multinational prevalence survey" study indicate the existence of significant variations in use, accessibility and satisfaction with health services by country and for socio-economic factors related to organizing and financing of care systems.